Preferred product attributes of a multipurpose vaginal ring: Findings from a phase 1 trial - Tolley, Elizabeth E.; Hanif, Homaira; Thurman, Andrea; Brache, Vivian; Doncel, Gustavo F. (Frontiers in Reproductive Health, 2023)
Most women face multiple and co-occurring risks from unwanted pregnancy, human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs) at some point during their lifetime. While a range of contraceptive methods exist and options for HIV prevention are increasing, to date, only male and female condoms provide multipurpose protection from both pregnancy and disease. From September 2017 to December 2018, 60 women from the United States and the Dominican Republic, randomized 1:1 to continuous or interrupted use and 4:1 to active versus placebo ring, participated in a Phase I trial to assess the safety and tolerability of a three-month multipurpose intravaginal ring (IVR) containing the antiviral tenofovir and the contraceptive levonorgestrel. This study examines survey responses from all participants and qualitative data from a subset of 17 women to assess acceptability of and preferences for IVR characteristics. Overall, women liked the concept of a multipurpose IVR and found it easy to insert and remove. Initial concerns about the size or thickness of the ring generally disappeared with use experience. Women weighed trade-offs between the ease of continuous use for a longer duration against concerns about hygiene and discoloration of the ring when left in place during menses. Whether randomized to continuous or interrupted use, most women found ring attributes (size, thickness, flexibility) very acceptable. They provided recommendations via survey and qualitative interviews for ring modifications that would further increase acceptability. Insights into women’s use experiences also suggest the need for clear counseling messages and introduction strategies that can facilitate women’s choice and use of prevention methods. Study findings suggest that a multipurpose IVR would make a valuable contribution to women’s sexual and reproductive health options, and that both continuous and interrupted use strategies may be preferred.